2006
DOI: 10.4025/actascibiolsci.v28i2.1041
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia do esôfago e do papo de perdizes <em>Rhynchotus rufescens</em> (Tiramidae)

Abstract: ABSTRACT. Twenty adult partridges Rhynchotus rufescens were used to study the morphology of oesophagus and crop. Materials to the morphologic study were collected and lengths of the oesophagus and of the crop were measured. For histological study, fragments of the oesophagus and of the crop were stained routinely with Masson's trichrome stain. Total oesophagus was larger in females. In the entrance of the thorax, its ventral wall is enlarged broadly, forming the crop, which is larger in males. Oesophagus mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Several investigations found that the functional association, despite showing no convergence across avian species, could not be discarded according to the absence of these glands in the context of our study. In contrast, the esophagus of Lanius tephronotus (Zhu, 2015b), Gallus gallus domesticus (Ventura et al, 2013), Rhynchotus rufescens (Rossi et al, 2006), Ross broiler chickens (Mobini, 2014), Columba livia (Kausar, 2019), and Meleagris gallopavo (Yovchev & Penchev, 2019) has mucous glands in both the cervical and thoracic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations found that the functional association, despite showing no convergence across avian species, could not be discarded according to the absence of these glands in the context of our study. In contrast, the esophagus of Lanius tephronotus (Zhu, 2015b), Gallus gallus domesticus (Ventura et al, 2013), Rhynchotus rufescens (Rossi et al, 2006), Ross broiler chickens (Mobini, 2014), Columba livia (Kausar, 2019), and Meleagris gallopavo (Yovchev & Penchev, 2019) has mucous glands in both the cervical and thoracic regions.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings revealed that the oesophagus of the quail was divided into three parts; cervical, crop and thoracic parts similar to those reported in quails (Wilkinson et al., 2018; Zaher et al., 2012), common quail (Parchami & Dehkordi, 2011), rock doves (Shawki et al., 2021), Eurasian collared doves (El‐Mansi et al., 2021), homing pigeon (Kadhim & Mohamed, 2015), guinea fowl (Gosomji et al., 2016), geese (Shehan, 2012), Grey‐Backed Shrike (Zhu, 2015), partridge (Rossi et al., 2006) and white stork (Rus et al., 2000). In contrast, the oesophagus of captive bustards (Bailey et al., 1997), rheas (Rodrigues et al., 2012) and white‐breasted kingfisher (Al Kinany, 2017) consists of two parts; cervical and thoracic, with no crop.…”
Section: Discussionmentioning
confidence: 99%
“…It is formed of cervical and thoracic parts in addition to the crop (Zhu, 2015). The avian crop ( ingluvies ) is represented by a dilated pouch of the cervical oesophagus immediately before entering the thoracic cavity (Hashem, 2018; Rossi et al., 2006; Zaher et al., 2012). Its wall is associated to the skin and to the clavicle ( clavicula s. furcular ) by loose connective tissue, additionally to the sternum by musculus compressor ingluvialis (Langenfeld, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation